2017
DOI: 10.1111/hdi.12596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the functions of the temporary catheter with various tip types

Abstract: Introduction: A temporary catheter (TC) is used short-term and for emergencies. There are some cases when we cannot withdraw blood immediately after inserting the catheter in our patients. The reason is said to be the tips of the TC sticking to the vascular walls.Objective: We evaluated examined 3 catheters with different tip shapes in a simulation circuit to assess the effect on the blood flow.Methods: Water was circulated in the simulation circuit at 1 L/minute. Next, we inserted each TC into the model, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…They are easier to place. Even if they provide a lower flow rate, they provide sufficient blood flow for hemodialysis as long as there is no malposition [8].…”
Section: Discussionmentioning
confidence: 99%
“…They are easier to place. Even if they provide a lower flow rate, they provide sufficient blood flow for hemodialysis as long as there is no malposition [8].…”
Section: Discussionmentioning
confidence: 99%
“…While there are numerous reports of clinical [20][21][22] and animal studies 23 conducted to evaluate recirculation in long-term catheters (tunneled cuffed-type catheters), only a few similar studies, including clinical 24 and in vitro 25 studies, have been conducted for temporary indwelling catheters. The tip structure of the catheter is one of the most important factors influencing recirculation; recirculation reduces the removal performance of hemodialysis, and is expected to be similar regardless of whether the catheter used is a long-term catheter or a temporary catheter.…”
Section: Discussionmentioning
confidence: 99%
“…In a related investigation using a fluid experiment, we observed that the fluid in blood vessels changes if the catheter tip structures are different. 6 The impact of adhesion due to the catheter tip's structure should be considered when a dialysis catheter is being selected. The split steam catheter that was used for the present patient has separate blood removal and auto-transfusion sections.…”
Section: Discussionmentioning
confidence: 99%
“…In a related investigation using a fluid experiment, we observed that the fluid in blood vessels changes if the catheter tip structures are different. 6…”
Section: Discussionmentioning
confidence: 99%